Sources and dynamics of fecal pollution and antibiotic resistance across a Mediterranean land–sea continuum - Angela Freddi; Marco Basili; Antonella Penna; Silvia Casabianca; Ben J. Tscharke; Metasebia Gebrewold; Stuart L. Simpson; Elena Manini; Warish Ahmed (Journal of Environmental Management, 2026)

Impact of wildfires on sediment quality in estuaries in New South Wales, Australia - Thayanne L. Barros; Mariana Mayer-Pinto; Katherine A. Dafforn; Stuart L. Simpson; Mark Farrell; Sally A. Bracewell; Emma L. Johnston (Chemosphere, 2025)

In Situ isotope tracing for metal bioaccumulation in open waters: Implications for interpreting biomonitoring data and safe seafood aquaculture - Haiyan Xiong; Tao Wang; Xue Cao; Jing Qian; Stuart L. Simpson; Rong Chen; Qiao-Guo Tan; Minwei Xie (Journal of Hazardous Materials, 2025)

Hydrodynamic perturbations on contaminant behavior in low-permeability sediments: porewater metal dynamics and risk assessment implications - Ning Wang; Hongwei Hu; Wenze Xiao; Qiao-Guo Tan; Rong Chen; Minwei Xie; Stuart L. Simpson (Environmental Pollution, 2025)

A highly prevalent and specific cryptic plasmid pBI143 for human fecal pollution tracking in a subtropical urban river - Yawen Liu; Wendy J.M. Smith; Metasebia Gebrewold; Rory Verhagen; Stephen Cook; Stuart L. Simpson; Bethany Oceguera Johnson; Kyle Bibby; Warish Ahmed (Water Research, 2025)

Development and comparative assessment of RT-qPCR and duplex RT-LAMP assays for the monitoring of Aichi virus A (AiV-A) in untreated wastewater samples - Mariah C.A. do Nascimento; Wendy J.M. Smith; Yawen Liu; Stuart L. Simpson; Aaron Bivins; Paula Rahal; Warish Ahmed (Science of The Total Environment, 2024)

Development and evaluation of a colorimetric LAMP based-assay targeting the Bacteroides HF183 marker for tracking sewage pollution in environmental waters - Mariah C.A. do Nascimento; Wendy J.M. Smith; Metasebia Gebrewold; Yawen Liu; Stuart L. Simpson; Aaron Bivins; Paula Rahal; Warish Ahmed (Water Research, 2024)

Site-specific risk-based threshold (RBT) concentrations for sewage-associated markers in estuarine swimming waters - Warish Ahmed; Mary E. Schoen; Jeffrey Soller; Joanna Ciol Harrison; Kerry A. Hamilton; Metasebia Gebrwold; Stuart L. Simpson; Sudhi Payyappat; Michele Cassidy; Nathan Harrison; Colin Besley (Science of The Total Environment, 2024)

Comparison of adsorption-extraction (AE) workflows for improved measurements of viral and bacterial nucleic acid in untreated wastewater - Jesmin Akter; Wendy J.M. Smith; Yawen Liu; Ilho Kim; Stuart L. Simpson; Phong Thai; Asja Korajkic; Warish Ahmed (Science of The Total Environment, 2024)

Evaluation of colorimetric RT-LAMP for screening of SARS-CoV-2 in untreated wastewater - Jesmin Akter; Wendy J.M. Smith; Metasebia Gebrewold; Ilho Kim; Stuart L. Simpson; Aaron Bivins; Warish Ahmed (Science of The Total Environment, 2024)

Comparison of concentration and extraction workflows for qPCR quantification of intI1 and vanA in untreated wastewater - Yawen Liu; Wendy Smith; Metasebia Gebrewold; Xinhong Wang; Stuart L. Simpson; Aaron Bivins; Warish Ahmed (Science of The Total Environment, 2023)

Improving toxicity prediction of metal-contaminated sediments by incorporating sediment properties - Yanfeng Zhang; Minwei Xie; David M. Spadaro; Stuart L. Simpson (Environmental Pollution, 2023)

Unveiling indicator, enteric, and respiratory viruses in aircraft lavatory wastewater using adsorption-extraction and Nanotrap® Microbiome A Particles workflows - Warish Ahmed; Wendy J.M. Smith; Ananda Tiwari; Aaron Bivins; Stuart L. Simpson (Science of The Total Environment, 2023)

The distribution of metal and petroleum-derived contaminants within sediments around oil and gas infrastructure in the Gippsland Basin, Australia - Sharon E. Hook; Scott Foster; Franziska Althaus; Douglas Bearham; Brad M. Angel; Andrew T. Revill; Stuart L. Simpson; Joanna Strzelecki; Tom Cresswell; Keith R. Hayes (Marine Pollution Bulletin, 2023)

Occurrence of multiple respiratory viruses in wastewater in Queensland, Australia: Potential for community disease surveillance - Warish Ahmed; Aaron Bivins; Mikayla Stephens; Suzanne Metcalfe; Wendy J.M. Smith; Kwanrawee Sirikanchana; Masaaki Kitajima; Stuart L. Simpson (Science of The Total Environment, 2023)

Comparative analysis of Adsorption-Extraction (AE) and Nanotrap® Magnetic Virus Particles (NMVP) workflows for the recovery of endogenous enveloped and non-enveloped viruses in wastewater - Warish Ahmed; Aaron Bivins; Asja Korajkic; Suzanne Metcalfe; Wendy J.M. Smith; Stuart L. Simpson (Science of The Total Environment, 2023)

Contaminant pulse following wildfire is associated with shifts in estuarine benthic communities - Sally A. Bracewell; Thayanne L. Barros; Mariana Mayer-Pinto; Katherine A. Dafforn; Stuart L. Simpson; Emma L. Johnston (Environmental Pollution, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Organic carbon and salinity affect desorption of PFAS from estuarine sediments - Divina A. Navarro; Danielle P. Oliver; Stuart L. Simpson; Rai S. Kookana (Journal of Soils and Sediments, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Using meta‐omics of contaminated sediments to monitor changes in pathways relevant to climate regulation - Simone C. Birrer; Katherine A. Dafforn; Melanie Y. Sun; Rohan B. H. Williams; Jaimie Potts; Peter Scanes; Brendan P. Kelaher; Stuart L. Simpson; Staffan Kjelleberg; Sanjay Swarup; Peter Steinberg; Emma L. Johnston (Environmental Microbiology, 2019)
Summary Microbially mediated biogeochemical processes are crucial for climate regulation and may be disrupted by anthropogenic contaminants. To better manage contaminants, we need tools that make real‐time causal links between stressors and altered microbial functions, and the potential consequences for ecosystem services such as climate regulation. In a manipulative field experiment, we used metatranscriptomics to investigate the impact of excess organic enrichment and metal contamination on the gene expression of nitrogen and sulfur metabolisms in coastal sediments. Our gene expression data suggest that excess organic enrichment results in (i) higher transcript levels of genes involved in the production of toxic ammonia and hydrogen sulfide and (ii) lower transcript levels associated with the degradation of a greenhouse gas (nitrous oxide). However, metal contamination did not have any significant impact on gene expression. We reveal the genetic mechanisms that may lead to altered productivity and greenhouse gas production in coastal sediments due to anthropogenic contaminants. Our data highlight the applicability of metatranscriptomics as a management tool that provides an immense breadth of information and can identify potentially impacted process measurements that need further investigation.

Scientific Considerations for the Assessment and Management of Mine Tailings Disposal in the Deep Sea - Lindsay L. Vare; Maria C. Baker; John A. Howe; Lisa A. Levin; Carlos Neira; Eva Z. Ramirez-Llodra; Amanda Reichelt-Brushett; Ashley A. Rowden; Tracy M. Shimmield; Stuart L. Simpson; Eulogio H. Soto (Frontiers in Marine Science, 2018)

Challenges for using quantitative PCR test batteries as a TIE-type approach to identify metal exposure in benthic invertebrates - Sharon E. Hook; Hannah L. Osborn; David A. Spadaro; Stuart L. Simpson (Environmental Science and Pollution Research, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Long-term copper partitioning of metal-spiked sediments used in outdoor mesocosms - Stephanie Gardham; Grant C. Hose; Stuart L. Simpson; Chad Jarolimek; Anthony A. Chariton (Environmental Science and Pollution Research, 2014)

Challenges in understanding the sources of bioaccumulated metals in biota inhabiting turbid river systems - Tom Cresswell; Ross E. W. Smith; Stuart L. Simpson (Environmental Science and Pollution Research, 2014)

Challenges with tracing the fate and speciation of mine-derived metals in turbid river systems: implications for bioavailability - Tom Cresswell; Ross E. W. Smith; Dayanthi Nugegoda; Stuart L. Simpson (Environmental Science and Pollution Research, 2013)

An Assessment of Three Harpacticoid Copepod Species for Use in Ecotoxicological Testing - Daniel J. Ward; Victor Perez-Landa; David A. Spadaro; Stuart L. Simpson; Dianne F. Jolley (Archives of Environmental Contamination and Toxicology, 2011)